The State of the Cardiovascular System in Type 2 Diabetes Patients Who Have Undergone COVID-19 (Eurasian Research Bulletin, 2024)
The COVID-19 pandemic caused by the novel coronavirus SARS-CoV-2 has had a significant impact on global health, affecting millions of individuals worldwide. Emerging evidence suggests a potential link between COVID-19 and various cardiovascular complications, as well as an exacerbation of existing comorbidities such as type 2 diabetes mellitus (T2DM). Type 2 diabetes (T2D) patients are known to be at an increased risk of developing severe complications from COVID-19. Among these complications, cardiovascular involvement has been widely reported. This research article aims to explore the state of the cardiovascular system and clinical features of T2DM following COVID-19, highlighting the potential mechanisms, implications, and management strategies.